قاعدة على اليد ما أخذت حتى تؤديه: دراسة تأصيلية تطبيقية في ضوء الأحكام الصادرة من الدوائر التجارية بديوان المظالم - ابن شبيب، أحمد بن عبدالعزيز (الرئاسة العامة للبحوث العلمية والافتاء, 2017)
هذا البحث يعنى بدراسة قاعدة (على اليد ما أخذت حتى تؤديه) من الجانب التأصيلي، وكذلك تطبيقاتها لدى الدوائر التجارية بديوان المظالم. وقد جاء في مبحثين، أما المبحث الأول: فقد عني بالجانب التأصيلي للقاعدة من حيث بيان معناها الإفرادي والإجمالي، وأركانها، ومصدرها، وصيغها، ومظانها، ثم كان الحديث عن حالات وصور تطبيق القاعدة، وتم حصرها في حالتين: الحالة الأولى: بقاء العين المعينة: ففي هذه الحالة يجب رد العين إلى صاحبها مطلقاً بالإجماع. الحالة الثانية: حال تلف العين، وهذه الحالة لا تخلو من إحدى صورتين: الصورة الأولى: أن يكون التلف بسبب تعد أو تفريط ممن كانت العين تحت يده: ففي هذه الصورة هو ضامن دائماً بالإجماع. الصورة الثانية: أن يكون التلف قد حدث بدون تعد ولا تفريط ممن كانت العين تحت يده: ففي هذه الصورة اختلف العلماء في القول بتضمن صاحب اليد، والقول الراجح في ذلك: أن صاحب اليد يضمن إن كانت يده يد ضمان مطلقاً، ولا يضمن صاحب يد الأمانة مطلقاً -ومنها اليد في العارية-. ثم جاء الحديث بشكل مقتضب عن مسألة ضمان الأيدي المترتبة على يد الضامن وتم تخريجها على مسألة حكم الأيدي المترتبة على يد الغاصب. أما المبحث الثاني: فقد عني بعرض التطبيقات القضائية لدى الدوائر التجارية بديوان المظالم، وتم تقسيمه إلى مطلبين، أحدهما: للحديث عن التطبيقات لحالات وصور القاعدة، وجاءت تطبيقات على يد الناقل ويد السمسار ويد الشريك، وثانيهما: التطبيقات لاختلاف طريقة الاستناد للقاعدة، وجاءت تطبيقات على أنها حديث نبوي وقاعدة فقهية وأنها من الأمور المقررة شرعاً وأن مؤداها مما استقر عليه عمل ديوان المظالم. This research deals with the rule (the hand that takes is responsible for what it has taken until it returns it) from the fundamental aspect, as well as its applications in the business sections at the Diwan of Grievances. It comprises two themes. The first theme deals with the fundamental aspect of the rule in terms of its individual and general meaning, pillars, source, formulas and recourses. Then, it discusses the cases and forms of the implementation of the rule, as they are identified in the following two cases: First case: The survival of the specified property: in this case, the property must be unanimously returned to the owner. Second case: The damage of the property, a case of two manifestations: First manifestation: the damage is due to infringement or negligence by the person who controls the property. In this case, he is permanently the guarantor by consensus. Second manifestation: the damage has occurred without infringement or negligence by the person who controls the property, in which case, the scholars differed in saying whether the person in control of the property is the guarantor or not, but the preponderant saying is that the person in control should guarantee if his control is an absolute guarantee, and the person in control does not guarantee the trust in an absolute manner, including the borrowed items. Then, it discusses in brief the issue of the control guarantee entailed upon the control of the guarantor, which was interpreted according to the issue of control ruling entailed upon the control of a usurper. The second theme deals with presenting the judicial applications in the business sections at the Diwan of Grievances and it is divided into two topics. The first one discusses the applications of the cases and forms of the rule, including applications to the control of transferor, broker and partner. The second discusses the application of the different way to refer to the rule, including applications to the rule as a prophetic hadith, a jurisprudential rule, and as one of the matters that are approved in sharia and on which the work of the Diwan of Grievances is based.
Keywords: الفقه الإسلامي -- القواعد الفقهية -- الأحكام القضائية -- الدوائر التجارية